Problem of shadow in the Lobachevski space - Kostin, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We consider the problem of shadow in a hyperbolic space. This problem can be regarded as a problem of finding conditions guaranteeing that points belong to a generalized convex hull of the family of balls.